Transforming Social Capital into Economic Capital: An Analysis of PT EAHM's Multi-Level Marketing Strategy for Cahaya Biscuits from the Perspective of Progressive Islamic Marketing - Hasanah, Uswatun; Handriani, Eka (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
This research analyzes the marketing phenomenon of